The Hexahelix Model in the Prevention and Eradication of Narcotics Abuse in Bandung City - Roy Febriansyah; Ramaditya Rahardian; Meti Mediyastuti Sofyan; Rikki Maulana Yusup (Spirit Publik: Jurnal Administrasi Publik, 2025)
The problem of drug abuse and illicit drug trafficking in Bandung City is a strategic issue that requires a collaborative response across sectors. This study aims to analyse the implementation of Collaborative Governance within the Hexa Helix Model in the execution of the National P4GN Programme by the Bandung City Narcotics Control Board (BNN). The approach used is qualitative interpretative, with data collection techniques including in-depth interviews, observations, and document reviews involving six key actors: government, academia, the private sector, civil society, media, and legal entities. Data analysis is based on the interactive model by Miles, Huberman, and Saldana. The results indicate that the five dimensions of Collaborative Governance according to Ansell and Gash starting condition, facilitative leadership, institutional design, collaborative process, and intermediate outcomes have been implemented in the collaboration between the BNN and the actors. The BNN acts as a facilitator in collaborative forums, agreement formulation, and the implementation of preventive programmes such as socialisation, training, mass urine testing, and the establishment of the Bersinar neighbourhood. Although this collaboration shows positive initial results, challenges still arise, such as limited resources, differences in interests, and the absence of mutually agreed evaluation indicators. This study concludes that the Hexa Helix Model is effective in strengthening synergy among stakeholders, but its sustainability requires strengthened commitment, institutional reforms, and the formulation of measurable and mutually agreed-upon performance indicators.